Management of intertrochanteric femur fracture by proximal femoral nail and its functional outcome: A prospective study - Satish Divakar Mehta; Rahil Jiwani; Abhijit Maruti Kadam; Bharat Pawar (Asian Journal of Medical Sciences, 2022)
Background: Intertrochanteric fractures are commonly encountered in orthopedics practice. Achieving early mobilization in patients with intertrochanteric fractures is the cornerstone of management. Proximal femoral nailing (PFN) is gaining popularity because of better tolerance of this procedure as well as minimal complication rates. We conducted this study to find out the functional outcome of patients with intertrochanteric fractures treated by PFN. Aims and Objectives: The objectives are as follows: (1) To find out the functional outcome of patients with intertrochanteric fractures treated by PFN. (2) To find out complications in patients treated by PFN. Materials and Methods: 60 patients with intertrochanteric fracture were included in this prospective study on the basis of a predefined inclusion and exclusion criteria. Under spinal anesthesia closed reduction and internal fixation by PFN were done. Open reduction was done in cases where closed reduction was not possible. Functional outcome as assessed by Harris hip score. Statistical analysis was done using SSPS 21.0 Software and P<0.05 was taken as statistically significant. Results: Out of 60 studied cases there were 37 (61.67%) males and 23 (38.33%) females with a M: F ratio of 1:0.62. The most common type of fracture was AO A3.2 (simple transverse fracture) which was seen in 28 (46.67%) patients followed by AO A3.1 (Simple Oblique fracture) and AO A3.3 (wedge fracture or multi-fragmentary fracture). Functional outcome was excellent to good in 41 (68.33%) patients whereas fair and poor outcome was seen in 12 (20%) and 5 (8.33%) patients, respectively. Very poor outcome was seen in 2 (3.33%) patients. Conclusion: PFN is an excellent technique for management of intertrochanteric fractures. It is associated with excellent outcome in majority of the cases and is associated with minimal complications.